Case Study Of Manager\'s Roles In Change Management In Media Prima Berhad (Towards Learning Organisations) - Wan Omar Sukri, Wan Laila Fatihah (2009)
This case study is concerned with identifying, from an organizational perspective the roles of manager\'s roles in change management in the largest integrated media investment group in Malaysia, Media Prima Bergad (MPB).